Effect of Mg doping on the growth aspects, crystalline perfection, and optical and thermal properties of congruent LiNbO3 single crystals. (25th October 2013) - Riscob, B.; Bhaumik, Indranil; Ganesamoorthy, S.; Bhatt, R.; Vijayan, N.; Karnal, A. K.; Wahab, M. A.; Bhagavannarayana, G.
<x xml:space="preserve">Abstract</x> Mg‐doped congruent lithium niobate single crystals were grown by the Czochralski technique. High‐quality single crystals were grown using a novel seeding technique in a resistive heating furnace. Analysis of crystalline perfection carried out by a multi‐crystal X‐ray diffractometer revealed that the grown crystals do not contain any structural grain boundaries but do contain point defects. The transmission characteristics showed an enhancement of band gap with an increase in Mg concentration. Conoscopy patterns revealed that the grown crystals are homogeneous and the incorporation of Mg into the lattice does not affect the optical sign (negative uniaxial) of the crystal. The refractive index measurements carried out using a prism coupler showed an increase in the optical birefringence (Δn), while the refractive index was found to decrease with the increase in doping concentration. Further, thermal conductivity was found to decrease with Mg incorporation in the lattice owing to phonon scattering from the Mg ions and, as a consequence, at high concentrations (>4 mol%) crack formation occurred. However, optimization of growth conditions reveals that a slower pulling rate leads to crack‐free lithium niobate crystals even at 6 mol% Mg doping.